Advances in the application of CRISPR technology in pathogen detection: amplification-based and amplification-free strategies - Zhou, Xiaoxing; Ye, Chao; Xie, Mengru; Wei, Yan; Zhao, Yilian; Liu, Xinchu; Ma, Jinghui; Qing, Jilin; Chen, Zhizhong (Frontiers in Cellular and Infection Microbiology, 2025)
CRISPR technology, with its high specificity and programmability, has become an important tool for the detection of human pathogens. The timely and accurate detection of pathogens is crucial for public health. In recent years, significant progress has been made in the application of CRISPR technology for pathogen detection. However, several challenges remain, including detection sensitivity, specificity, and operational convenience. This review summarizes the latest advances in CRISPR technology for pathogen detection, with a focus on the principles and performance comparisons of amplification-based CRISPR (such as those combined with isothermal amplification techniques like RPA and LAMP) and amplification-free CRISPR (such as cascade CRISPR, sensor technologies, and digital droplet CRISPR). It also discusses their applications in pathogen detection. In addition, the article analyzes the advantages and limitations of CRISPR detection technology and looks forward to future development trends, providing a theoretical basis for the optimization of rapid diagnostic techniques for pathogens.